Efek Resusitasi Jantung Paru Menggunakan Mechanical Chest Compressions Terhadap Keselamatan Pasien Henti Jantung - Sudiro Sudiro (Poltekkes Kemenkes Surakarta, 2020)
Background: Cardiac arrest is the biggest cause of death. The number of patients who survived is low. Data in the UK shows only 7% of patients who survived. The key factor to increase the amount of survival is the quality of cadiopulmonary resuscitation (CPR). CPR that is done manually or by humans tends to be of inferior quality due to fatigue. Mechanical chest compressions use machines and pistons to compress the chest, so that the frequency and depth of chest compression quality for a long time. The purpose of this systematic review is to analyze research evidence of the effect CPR using mechanical chest compressions to survival cardiac arrest. Methods : Systematic review is used to analyze the effectiveness of mechanical chest compressions against cardiac arrest. The article is traced from the data base of science direct, pub med, and EBSCO with the main keywords are mechanical chest compressions and cardiac arrest. Search on google search using the keywords mechanical chest compressions for cardiac arrest. Researchers only take research in the form of randomized controlled trials (RCT), and there are no language restrictions. The interventions carried out were mechanical chest compressions, measured outcomes were survival cardiac arrest, and side effects of the action. The quality of the study was assessed using the critical appaisal skill program. Data was synthesized based on the implementer, the intervention carried out, the blinding process, the results, conclusions and side effects of the action. Results: Findings in the form of 4 articles with high quality. The entire article states there is no difference in survival cardiac arrest between mechanical chest compressions and manual chest compressions. Mechanical chest compressions have more adverse side effects than manual chest compressions. Conclusion: The results of a systematic review show that mechanical chest compressions are no better than manual chest compressions, so they are not recommended for use.